Impact of Adrenaline or Cortisol Injection on Meat Quality Development of Merino Hoggets - Dario G Pighin; Sebastian A Cunzolo; Maria Zimerman; Adriana A Pazos; Ernesto Domingo; Anibal J Pordomingo; Gabriela Grigioni (Journal of Integrative Agriculture)
Increased levels of stress hormones in the muscle could lead to post mortem metabolic/structural modifications that could be reflected on meat quality. The present study investigated the metabolic effect of either adrenaline or cortisol injected into lambs in order to obtain an animal model of acute stress. Results showed that adrenaline or cortisol injection lead to glucose metabolism and muscle temperature increase. Muscle pH immediately post mortem was affected by adrenaline treatment. Water holding capacity (WHC) of fresh muscle, final muscle pH and temperature registered at 24 h post mortem were not affected by injected hormones. Hardness and adhesiveness of LD muscle evaluated 3 d post mortem tended to increase as a result of adrenaline or cortisol injection. Results demonstrated that injected hormones were able to affect the post mortem muscle biochemistry and the pH/T curve independently of final muscle pH.